Spray tips and adjuvant in the spectrum of spray droplets in pitaya (Hylocereus costaricensis) cultivation - Luã Lukas França Sousaa; Edison Masato Santana Miyagawa; Cristiane Fernandes Lisboa; Fernanda Lamede Ferreira de Jesus; Adriano Bicioni Pacheco; Nara SilveiraVelloso; Túlio de Almeida Machado (Dyna, 2022)
This study aimed to evaluate the spectrum of droplets produced by three spray tips (JSF 11002, SF 11001, and JD12) using two types of spray solutions (with and without adjuvant). The experiment was conducted in randomized blocks in a 3×2 factorial scheme, with four replications. The targets were scanned after spraying and later analyzed by the free software Conta-Gotas. Values were extracted from the number of droplets, number of diameter, dispersion, volume, density, coverage, DV10, DV50, and DV90. Adjuvant addition increased droplet diameter and coverage, thus being indicated to reduce drift losses. The tips JSF 11002 and JD12 showed a larger droplet size, representing higher risk of runoff and low penetration into the plant canopy. The tip SF 11001 presented better penetration and fixation in the plant, thus being the most recommended for the application of phytosanitary products in pitaya.